2015
DOI: 10.1016/j.envres.2015.03.027
|View full text |Cite
|
Sign up to set email alerts
|

Microbial diversity in bioaerosol samples causing ODTS compared to reference bioaerosol samples as measured using Illumina sequencing and MALDI-TOF

Abstract: The importance of the microbial diversity of bioaerosols in relation to occupational exposure and work related health symptoms is not known. The aim of this paper is to gain knowledge on the bacterial and fungal communities in dust causing organic dust toxic syndrome (ODTS) and in reference dust not causing ODTS. Bacterial and fungal communities were described in personal exposure samples from grass seed workers developing ODTS, in dust generated from grass seeds causing ODTS and in dust generated from referen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
62
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(66 citation statements)
references
References 73 publications
4
62
0
Order By: Relevance
“…Bacteria found in the atmosphere are diverse. Airborne bacterial assemblages in both terrestrial and marine environments contain more than 150 genera of bacteria [21,22,23], a level of diversity comparable to other nutrient poor environments such as Antarctic snow, which has been shown to contain in the region of 250 genera of bacteria [24]. Barberán et al [25] collated over 1000 sampling efforts and found more than 110,000 different species of airborne bacteria in the USA alone.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bacteria found in the atmosphere are diverse. Airborne bacterial assemblages in both terrestrial and marine environments contain more than 150 genera of bacteria [21,22,23], a level of diversity comparable to other nutrient poor environments such as Antarctic snow, which has been shown to contain in the region of 250 genera of bacteria [24]. Barberán et al [25] collated over 1000 sampling efforts and found more than 110,000 different species of airborne bacteria in the USA alone.…”
Section: Introductionmentioning
confidence: 99%
“…Barberán et al [25] collated over 1000 sampling efforts and found more than 110,000 different species of airborne bacteria in the USA alone. Most bacterial communities in the atmosphere comprise four main phyla: Actinobacteria, Bacteroidetes, Firmicutes, and Proteobacteria, a fact that remains consistent in the atmosphere surrounding both marine and terrestrial habitats [23,26]. However, aerial microbial diversity at genus level is more variable and depends on environmental conditions, such as proximity to agricultural sites, meteorological conditions and season [18,22].…”
Section: Introductionmentioning
confidence: 99%
“…A previous study found that there is trypsin and trypsin-like enzyme activity in extracted tissue samples from crustaceans (Sun and Lopata 2010), but there are no previous publications that have quantified the level of airborne trypsin activity during seafood processing. Trypsin is a common serine protease enzyme and inhaled by workers may have an immunological or non-immunological effect on the lungs (Sun and Lopata 2010;Baur 2005;Florsheim et al 2015;Madsen et al 2015). Optimal conditions for several crustacean trypsins are around 40˚C and pH6, which is close to the physiological conditions found in human lungs (Sun and Lopata 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Endotoxin levels of 1350 EU/m 3 have been reported in herring industry (Bang et al 2005). Endotoxins are suggested to be a cause of occupational respiratory symptoms in occupational settings including among seafood processing workers (Sigsgaard and Schlunssen 2004;Sherson, Hansen, and Sigsgaard 1989;Madsen et al 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation